Multiuser detection in multipath environments for variable spreading-factor CDMA systems. - Boariu, A.
A way to allow variable data rates in CDMA is by varying the spreading factor in accordance with the data rate requested by the user. A detection scheme suitable for multirate transmission is required in addition to one that combats multiple access interference of other users and intersymbol interference from multipath. In this letter, an energy-add multiuser detection method is combined with a scheme called Cholesky-iterative detection to cope with these challenges. It allows the users to be estimated on a symbol-by-symbol basis, making receiver complexity independent of data package length. Simulation results correspond closely to a single-user lower bound. The results also show that the bit-error probability performances of the various users for the Cholesky-iterative detector are closely clustered, while those of a previously published scheme, decorrelation feedback detection, are more widely spread
Keywords: Cholesky-iterative detection; Bit-error probability performance; Data package length; Energy-add multiuser detection method; Intersymbol interference; Multipath; Multipath environments; Multiple access interference; Multirate transmission; Receiver complexity; Variable data rates; Variable spreading-factor CDMA systems